Determinan pembiayaan murabahah dengan non-performing financing sebagai variabel moderating - Nauval, Amiratun; Rahman, Taufikur (Journal of Accounting and Digital Finance, 2021)
This study aims to determine the effect of third-party funds, capital adequacy ratio, and return on assets on murabahah financing with non-performing financing as moderating variables. This type of research is a quantitative research using secondary data. The population in this study amounted to 14 Islamic commercial banks. The sample of this study was determined by the purposive sampling method with the criteria determined by the researcher to obtain 60 samples from 12 Islamic commercial banks in the 2016-2020 period. The results showed that the third-party funds and capital adequacy ratio variables positively and significantly affected murabahah financing. In contrast, the return on assets variable had a positive but not significant effect. The moderated regression analysis (MRA) test shows that the non-performing financing interaction can moderate the effect of third-party funds, capital adequacy ratio, and return on assets on murabahah financing.